1988
DOI: 10.3181/00379727-188-42750
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Acts in the Brain to Mediate Seasonal Steroid Inhibition of Luteinizing Hormone Secretion in the White-Footed Mouse (Peromyscus leucopus)

Abstract: A melatonin-induced supersensitivity of the gonadotropin-secretory system to the negative feedback action of sex steroids is thought to be important to the timing of seasonal reproduction. However, little is knownconcerning this action of melatonin. In the present study the antigonadal action of melatonin in the anterior hypothalamus (AH) of the white-footed mouse, Peromyscus leucopus, was used to examine the neuroendocrine mechanism whereby melatonin enhances the sensitivity to sex steroid negative feedback. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 11 publications
(15 reference statements)
1
14
2
Order By: Relevance
“…Studies using intracerebral melatonin implants have however indicated that the photoperiodic effects of melatonin are mediated via a site in or near the hypothalamus (10)(11)(12). The results of the present study show discretely localized high-affinity melatonin receptors restricted to the hypothalamus and epithalamus of the brain and the purs tuberalis of the pituitary.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Studies using intracerebral melatonin implants have however indicated that the photoperiodic effects of melatonin are mediated via a site in or near the hypothalamus (10)(11)(12). The results of the present study show discretely localized high-affinity melatonin receptors restricted to the hypothalamus and epithalamus of the brain and the purs tuberalis of the pituitary.…”
Section: Discussionsupporting
confidence: 55%
“…The localization of these low-affinity receptors within the brain, pituitary and other tissues is remarkably ubiquitous and, as yet, their physiological significance is unknown (4)(5)(6)(7)(8)(9). The widespread distribution found for the low-affinity melatonin receptor contrasts with reports that the photoperiodic effects of melatonin can only be induced by very localized intracerebral administration of the compound (10)(11)(12).…”
contrasting
confidence: 39%
“…We assessed effects of 6-MBOA on reproductive parameters and DTH in long-day breeding whitefooted mice. This species was chosen because individuals i) exhibit seasonal changes in immune activity and reproductive capacity (Johnston et al 1980b;Pyter et al 2005b), ii) some of these changes are mediated by melatonin (Johnston et al 1980a;Glass et al 1988), and iii) individuals consume a variety of foods in the wild, including plants (King 1968). Other species known to be sensitive reproductively to 6-MBOA have not been as well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Tissues were homogenized in 1 N acetic acid and 20 mM hydrochloride and were eluted through a SepPak C18 cartridge (Waters Associates, Milford, Massachusetts, USA) (30). Blood was sampled from the retroorbital sinus of mice under slight anesthesia with ether.…”
Section: Methodsmentioning
confidence: 99%